2014
DOI: 10.1242/jcs.137422
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of the disease-related L78R mutation for dimerization and activity of STAT3

Abstract: Signal transducer and activator of transcription 3 (STAT3) is a transcription factor that is centrally involved in diverse processes including haematopoiesis, immunity and cancer progression. In response to cytokine stimulation, STAT3 is activated through phosphorylation of a single tyrosine residue. The phosphorylated STAT3 dimers are stabilized by intermolecular interactions between SH2 domains and phosphotyrosine. These activated dimers accumulate in the nucleus and bind to specific DNA sequences, resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(62 citation statements)
references
References 55 publications
9
53
0
Order By: Relevance
“…We further showed that the STAT3 NTD mediates cooperativity via the conserved handshake dimer interface (Fig. 8B and C) rather than the Ni 2ϩ interface, consistent with reported mutagenesis data for STAT family members (13,20,54,(56)(57)(58)(59)(60)(61). The data suggest a structural model of two STAT3 dimers on tandem DNA sites "holding hands" by NTD dimerization in a syn geometric arrangement (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We further showed that the STAT3 NTD mediates cooperativity via the conserved handshake dimer interface (Fig. 8B and C) rather than the Ni 2ϩ interface, consistent with reported mutagenesis data for STAT family members (13,20,54,(56)(57)(58)(59)(60)(61). The data suggest a structural model of two STAT3 dimers on tandem DNA sites "holding hands" by NTD dimerization in a syn geometric arrangement (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, a peptide mimetic of the ␣2 helix in the handshake interface induced apoptosis of breast and prostate cancer cells but not normal cells (7,18,71). A somatic mutation in this interface (Leu 78 Arg) has been found in inflammatory hepatocellular adenoma, where it disrupts homotypic interactions between unphosphorylated STAT3 dimers (20). This suggests that targeting the NTD handshake interface may selectively inhibit the expression of a subset of genes normally regulated by unphosphorylated STAT3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Interestingly, their findings support a direct interaction between the two Nterminal domains, in agreement with previous studies reporting the significance of N-terminal domain for USTATs dimerization. 22 Given the increased interest in the dimerization of USTAT3 and the availability of novel biophysical data, in this study we used an integrative modeling approach to investigate structure and dynamics of 6 this macromolecular assembly.…”
supporting
confidence: 90%
“…Interestingly, substitution of the corresponding Y631 to phenylalanine in STAT2 promotes type I IFN signaling [29,30]. The three other mutations found in IHCA were distributed throughout the protein: the altered leucine-78, which disturbs latent dimer formation [31,32]; glutamate-166, which is part of helix alpha 1 involved in the interaction with gp130 [33]; and aspartate-502, which is located in the alpha-helical ''connector'' domain.…”
Section: Stat3 Mutationsmentioning
confidence: 99%